Kopciuszek: zagubiony szklany pantofelek i metamorfozy kobiecości - Gromkowska-Melosik, Agnieszka (Studia Edukacyjne, 2020)
The article is devoted to the reconstruction of Cinderella myth in contemporary culture in the relation to the changing concepts of femininity. The Author takes into account several contexts of this issue. First, it can be understood in the terms of life as a lottery thanks to which in one moment a person is famous or rich (e.g. thanks to television success). Also, the author analyses the Cinderella in a light of sociological theory of competitive mobility. Besides sociotherapeutic Cinderella complex is analysed as well as feminist interpretation of Cinderella are reconstructed. The different versions of Cinderella fable are confronted with the various kinds of relations between women and men in contemporary. The Author shows also the examples of using the Cinderella myth in commercial advertising as well as politics and economy (Cinderella industry).